Obstetric telemedicine during COVID-19 pandemic: Experience from teman ibu telemedicine for strengthening antenatal care - Dyah Krisnawati Satia Pratiwi; Brian Sahar Afifah (BKM Public Health and Community Medicine, 2021)
Objective: This paper explores midwives’role in developing yoga and pregnancy online class in the context of making pregnancy safer during COVID-19 pandemic, where obstetric telemedicine is more accessible as compared to face to face antenatal care. Content: Almost all over the world, antenatal care is restricted during COVID-19 pandemic, this risk delaying the progress of overcoming the danger signs of pregnancy which can lead to maternal mortality. In Indonesia, 90% of independent practice midwife services are closed and the coverage of K4 midwifery services antenatal care services for pregnant women 4 times during pregnancy continues to decline. Midwives’ have a strategic role in strengthening midwifery services through obstetric telemedicine, remote midwifery services from health facilities through audio and video. The services provided include antenatal care, classes for pregnant women including communication, information and education (KIE) on healthy lifestyles, as well as KIE COVID-19, and prenatal gentle yoga online, so as to provide safe, effective services, and minimize the risk of COVID-19 transmission. Within a year of the pandemic, temaniibu telemedicine provided service approximately 1,064 pregnant women from various regions in Indonesia through the Zoom meeting application. Technical barriers were found from users such as unstable internet signals, internal obstacles is such as unaccustomed in using electronic medical records, and the lack of insurance service providers that cover obstetric telemedicine services. Therefore, it is necessary to develop an Electronic Medica Record (EMR) and sustainable technology, in collaboration with donor and academia. Furthermore, the future of obstetric telemedicine can be used to strengthen health services during pandemic, since it reduces transportation usage to reach obstetric services, reduce waiting time for obstetric patients, and reduce the risk of maternal complications and newborn emergencies.